The circadian genes are required in DAL neurons for Drosophila long-term memory formation - Jerry C. P. Yin; Jerry C. P. Yin; Ethan Cui; Peter S. Johnstone; Deniz Top; Grace Boekhoff-Falk; Hong Zhou (Frontiers in Neuroscience, 2025)
We previously showed that memory formation of Drosophila olfactory avoidance can be inhibited by ubiquitous, post-training, inducible disruption of the circadian system. In this report, we limit intervention to the dorsal anterior lateral neurons, cells important for memory formation but not considered a part of the central clock. Post-training induction of “dominant negative” proteins or RNAi directed against either the clock or cycle genes in dorsal anterior lateral neurons disrupts 3-day memory. This experimental design minimizes indirect effects due to abnormal neuronal development, altered sensory processing at the time of training, effects of widespread ectopic expression of inhibiting proteins, and decreases the likelihood of “off-target” effects contributing to the disruption of memory. Induction prior to testing does not have any effect, likely ruling out an effect on retrieval. The transgene inductions mildly affect circadian locomotor rhythmicity and sleep but similarly to how these are affected in the parents of the progeny. Therefore, the effects on memory are very unlikely to be attributable to alterations in circadian locomotor activity or sleep. Paradoxically we also show that mutants in two of the circadian genes have normal 3-day memory. Thus, while global mutations in circadian genes do not impair memory formation, spatially and temporally restricted interventions in neurons do. We speculate that this discrepancy resembles a previously described developmental phenotype involving the central and a peripheral clock. In both contexts, systems-level compensation may allow events to occur independently of a functional circadian clock.